2007
DOI: 10.1007/s00421-006-0364-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of acute and 23 days of intermittent hypoxic exposures on the exercise-induced forehead sweating response

Abstract: The effect of acute and 23 days of intermittent exposures to normobaric hypoxia on the forehead sweating response during steady-state exercise was investigated. Eight endurance athletes slept in a normobaric hypoxic room for a minimum of 8 h per day at a simulated altitude equivalent to 2,700 m for 23 days (sleep high-train low regimen). Peak oxygen uptake (VO2(peak)) and peak work rate (WR(peak)) were determined under normoxic (20.9%O(2)) and hypoxic (13.5%O(2)) conditions prior to (pre-IHE), and immediately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
(40 reference statements)
3
19
0
Order By: Relevance
“…By contrast, the present fatigue-induced increase in relative work rate during prolonged exercise was not accompanied by such changes in the regulation of heat-loss responses, suggesting that acute changes of the relationship between relative and absolute work rate are not as a rule accompanied by modulations of sweating and cutaneous vasomotor tone. That ischaemia and hypoxaemia, but not fatigue, alter the regulation of heat loss during exercise supports the notion that such alterations may be triggered by stimulation of muscle metaboreceptors, as a result of reduced oxygen delivery to the working muscle (Kondo et al 1999;Eiken and Mekjavic 2004;Kacin et al 2005Kacin et al , 2007.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…By contrast, the present fatigue-induced increase in relative work rate during prolonged exercise was not accompanied by such changes in the regulation of heat-loss responses, suggesting that acute changes of the relationship between relative and absolute work rate are not as a rule accompanied by modulations of sweating and cutaneous vasomotor tone. That ischaemia and hypoxaemia, but not fatigue, alter the regulation of heat loss during exercise supports the notion that such alterations may be triggered by stimulation of muscle metaboreceptors, as a result of reduced oxygen delivery to the working muscle (Kondo et al 1999;Eiken and Mekjavic 2004;Kacin et al 2005Kacin et al , 2007.…”
Section: Discussionmentioning
confidence: 70%
“…In previous studies we have observed that increasing relative work rate during steady-load exercise, either by experimentally restricting blood flow to the contracting muscles (Eiken and Mekjavic 2004;Kacin et al 2005) or by introducing a hypoxic breathing gas (Kacin et al 2007), substantially potentiates the rate of sweating and attenuates skin blood flow. By contrast, the present fatigue-induced increase in relative work rate during prolonged exercise was not accompanied by such changes in the regulation of heat-loss responses, suggesting that acute changes of the relationship between relative and absolute work rate are not as a rule accompanied by modulations of sweating and cutaneous vasomotor tone.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Imakawa [14] and Kacin et al, [15] reported that if people performed endurance training at high attitude with the same intensity as that at sea level, the hypoxic stimulation to tissues at high altitude may be increased because of the relative exercise intensity being increased compared with that at sea level. In our study, the participants felt comfortable running at pace in normoxic conditions because of the effect of hypoxic training, which may have influenced the physiological exercise intensity of "fairly light" intensity.…”
Section: Open Accessmentioning
confidence: 99%